Impact of the Buffer/Absorber Interface on the Metastability of Fill Factor Temperature Coefficients in CIGSSe Solar Cells. Issue 20 (26th September 2021) - Ahmed, Hamsa; Solovyeva, Vita; Gonzalez, Marco A.; Elshabasi, Mohamed; Richter, Michael; Pareek, Devendra; Heise, Stephan J.; Stölzel, Marko; Weber, Alfons; Dalibor, Thomas; Schäfer, Sascha; Parisi, Jürgen
Abstract: The metastable behavior of the fill factor temperature coefficient (βFF, rel ) in Cu(In, Ga)(S, Se)2 solar cells is investigated for absorbers with a different Ga content in the front surface, and for different buffer materials. The buffer/absorber interface region is suggested to be the location which causes the metastability in βFF, rel . Temperature dependent current–voltage curves, light‐biased external quantum efficiency, and low temperature capacitance–voltage measurements are performed to characterize the electrical properties and metastable defects in the investigated solar cell devices. The presence of Ga in the absorber front surface, together with the buffer layer material plays a significant role in the metastable behavior. Additionally, energy dispersive X‐ray spectroscopy indicates that the In x S y buffer layers allow for elemental interdiffusion from absorbers with a Ga‐richer front surface, whereas a Zn(O, S) buffer shows to be rather resilient to atomic diffusion. The elemental interdiffusion between the buffer and absorber layers is proposed to be the cause of the defects causing the observed βFF, rel metastability. Abstract : The effect of the interface characteristics between Cu(In, Ga)(S, Se)2 (CIGSSe) absorbers and different buffer layers on metastability of fill factor temperature coefficients of CIGSSe solar cells is studied. Results indicate the presence of high density of DX centers in the absorber when gallium is present in its front surface, and an In x S y buffer layer is used.